Gastrointestinal obstruction by foreign bodies in a captive giant South American turtle (Podocnemis expansa) - Lescano G., Jesús (2015)
The case of a 4-year-old giant South American turtle (Podocnemis expansa) that presented anorexia, vomits and constipation during four days is reported. The animal was kept in a temperate land-water terrarium with gravel as substratum. The diet was only composed by commercial pelleted food for turtles. No alteration was observed during physical examination. Radiologic examination revealed multiple radio-opaque foreign bodies in the stomach. Gastric foreign body obstruction was diagnosed. Medical therapy was administered during seven days with limited success. Gastrotomy was performed and multiple stones of about 5 x 10 mm were removed. Then, the animal continued receiving medical therapy by means of prokinetic, analgesic and antibiotic drugs. The animal fully recovered.